(untitled) (Global Journal of Human-Social Science, 2025)
This article aims to determine the effect of inclusive finance on agricultural growth in sub-Saharan Africa. Using dynamic panel data from 31 SSA countries over the period from 2004 to 2020 and using the SYS-GMM of Blundell and Bond (1998) as an estimation technique, we determined the effect of finance inclusive on agricultural growth in sub-Saharan Africa. Overall, the results show that access to and use of financial services have negative effects on agricultural growth in Sub-Saharan Africa. We have issued some recommendations aimed at cleaning up the financial sector by putting in place infrastructures and reducing related transaction costs and facilitating access to credit, and even reforming the agrarian system in some of these countries.